FOODINFORMATICS OF VANILLIN-RICH DRINK AGAINST CANONICAL TARGETS OF BREAST CANCER - Karimi, Isaac; Yousefvand, Namdar; Shamspur, Tayebeh; Moloodi, Boshra (Universal Journal of Pharmaceutical Research, 2022)
Aim and objective: Vanillin-rich drink (Vimto®) is a popular drink among women. The aim of this study was to evaluate anti-breast cancer potential of Vimto®. Methods: the chemical composition of Vimto® has been determined by gas chromatography and foodinformatics used to identify its putative binders to canonical targets of breast cancer. The binding affinity (kcal/mol) of the target proteins of breast cancer and the phytocompounds was computationally obtained. Results: Major aliphatic hydrocarbons of Vimto® were hydroxymethyl furfurole, tetradecane, hexadecane, dodecane, octadecane and 9-octadecenamide while aromatic hydrocarbons were vanillin, benzoic acid, diisooctyl phthalate, butanoic acid, piperonal, bis (2-ethylhexyl) phthalate, and germacrene D. 9-octadecenamidebound firmly to HER2 (human epidermal growth factor receptor 2) and warrant experimental studies. All aromatic hydrocarbons expect benzoic acid and vanillin showed reliable BA with HER2. Germacrene D showed acceptable binding affinity with estrogen receptor alpha (ERα) and estrone sulfatase. Benzoic acid and diisooctyl phthalate showed strong BA with phosphoinositide 3-kinases (PI3Ks) and AKT (protein kinase B), respectively. Bis (2-ethylhexyl) phthalate and diisooctyl phthalate have been docked with HER2. Butanoic acid and bis (2-ethylhexyl) phthalate showed binding affinity with aromatase. Benzoic acid and diisooctyl phthalate, and bis (2-ethylhexyl) are not safe compounds while bounded to target proteins of breast cancer. Conclusions: To sum up, Vimto® is an amalgam of safe compounds possess possible anti-breast cancer, however it needs further experimental and biosafety evaluation. Peer Review History: Received: 6 December 2021; Revised: 7 January 2022; Accepted: 13 February, Available online: 15 March 2022 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewers: Dr. Rima Benatoui, Laboratory of Applied Neuroendocrinology, Department of Biology, Faculty of Science, Badji Mokhtar University Annaba, BP12 E L Hadjar–Algeria, benattouiryma@gmail.com Dr. U. S. Mahadeva Rao, Universiti Sultan Zainal Abidin, Terengganu Malaysia, raousm@gmail.com